Daya Tahan Rumah Tangga Petani terhadap Kekeringan di Jawa Timur dan Nusa Tenggara Barat - Bambang Sayaka; nFN Wahida; Tahlim Sudaryanto (Jurnal Agro Ekonomi, 2019)
EnglishExternal shock, such as drought, affects agricultural performance. Farmers External shock, such as drought, affects agricultural performance. Farmers should be resilient to external shock such that they keep producining or reducing risks amid climate uncertainty. This study was conducted in East Java and West Nusa Tenggara in 2016. Objectives of the study were: (a) to get data and information on drought affecting agricultural sector, especially, food crops and horticulture; (b) to estimate rice and chili farmers’ resilience to drought; and (c) to assess government policy performance and impacts related measures dealing with drought. The measurement method is the resilient index modified from the vulnerability index. In 2015 drought took place in most provinces in Indonesia and affected food yield ranging from lower yield to dried-up. Chili farmers’ resilience were better off than that of rice farmers in delaing with drought. The government tried to deal with drought through some effective actions, such as early warning to farmers, irrigation water allocation, Climate Field School, and water pump aid. Anticpatory and responsive measures are necessary such that drought impacts could be minimized.IndonesianGangguan eksternal seperti kekeringan sangat mempengaruhi kinerja sektor pertanian. Petani harus mempunyai daya tahan menghadapi gangguan eksternal agar tetap mampu berproduksi atau mengurangi risiko ditengah ketidakpastian iklim. Penelitian ini dilakukan di Jawa Timur dan Nusa Tenggara Barat pada tahun 2016. Tujuan penelitian adalah: (a) memperoleh data dan informasi tentang fenomena kekeringan sebagai salah satu faktor yang mempengaruhi sektor pertanian, khususnya pangan dan hortikultura; (b) mengukur daya tahan petani padi dan cabai terhadap dampak kekeringan; dan (c) mengetahui berbagai kinerja dan dampak kebijakan pemerintah dalam mengatasi kekeringan. Metode pengukuran dengan indeks daya tahan yang dimodifikasi dari vulnerability index. Pada tahun 2015 kekeringan melanda berbagai daerah di Indonesia menyebabkan hasil panen berkurang hingga puso. Daya tahan petani cabai umumnya lebih baik dari petani padi dalam menghadapi kekeringan. Pemerintah telah berusaha menanggulangi kekeringan antara lain dengan peringatan dini kepada petani, alokasi air irigasi, Sekolah Lapang Iklim, maupun bantuan pompa air. Tindakan antisipatif dan responsif perlu dilakukan agar dampak kekeringan dapat diminimalkan.